Grouping And Evaluation Of Financing Sources Of Cotton-Textile Clusters - Davlyatov Bekzodjon Aslankhojaevich (Genius Publishing Group, 2025)
This article talks about the external financing of cotton-textile clusters, as well as the main sources of financial relations between cluster member enterprises, the banking sector, various funds involved in the process.
Keywords: cluster; financing; innovation